Initial Outcomes of Laparoscopic Paraesophageal Hiatal Hernia Repair with Mesh. Issue 10 (October 2013) - Gebhart, Alana; Vu, Steven; Armstrong, Chris; Smith, Brian R.; Nguyen, Ninh T.
The use of mesh in laparoscopic paraesophageal hiatal hernia repair (LHR) may reduce the risk of late hernia recurrence. The aim of this study was to evaluate initial outcomes and recurrence rate of 92 patients who underwent LHR reinforced with a synthetic bioabsorbable mesh. Surgical approaches included LHR and Nissen fundoplication (n = 64), LHR without fundoplication (n = 10), reoperative LHR (n = 9), LHR with a bariatric operation (n = 6), and emergent LHR (n = 3). The mean length of hospital stay was 2 ± 3 days (range, 1 to 30 days). There were no conversions to open laparotomy and no intraoperative complications. One of 92 patients (1.1%) required intensive care unit stay. The 90-day mortality was zero. Minor complications occurred in 3.3 per cent, major complications in 2.2 per cent, and late complications in 5.5 per cent of patients. There were no perforations or early hernia recurrence. The 30-day reoperation rate was 1.1 per cent. For patients with available 1-year follow-up, the overall recurrence rate was 18.5 per cent with a mean follow-up of 30 months (range, 12 to 51 months). LHR repair with mesh is associated with low perioperative morbidity and no mortality. The use of bioabsorbable mesh appears to be safe with no early hiatal hernia recurrence or late mesh erosion. Longer follow-up is needed to determine the long-term rate of hernia recurrence associated with LHR with mesh.